Diet supplementation with a high dose of stearic acid to alleviate fish oil-induced milk fat depression in lactating ewes - Hervás G.; Toral P.G.; Frutos P. (Innovation for sustainability in sheep and goats, 2019)
Despite the benefits of using marine lipid supplements in dairy ewe diets to modulate milk fatty acid (FA) composition, this strategy causes milk fat depression (MFD), which precludes its use under farm conditions. This MFD is attributed to an impaired capacity of the mammary gland to achieve an adequate melting point for milk fat secretion. This alteration of fluidity has been linked to a shortage of available ruminal 18:0 caused by the consumption of marine lipids. However, in a previous study, we were not able to prevent the effects of fish oil supplementation through concomitant dietary addition of stearic acid (2% DM). Yet, before ruling out a mechanism based on milk fat fluidity, we decided to try with a higher dose of 18:0. Thus, this assay was conducted with 12 lactating ewes divided in 3 treatments that lasted for 4 weeks: a total mixed ration without lipid supplementation (control) or supplemented with 20 g/kg DM of fish oil alone (FO) or in combination with 40g/kg DM of 18:0 (FOSA-4). As expected, FO supplementation modified milk FA composition towards a healthier profile for consumers but, at the same time, reduced milk fat concentration. This MFD was not alleviated by the dietary addition of 4% 18:0 (FOSA-4). Depression of milk fat is discussed in relation to milk FA composition, particularly to the concentration of main metabolites responsible for changes in the melting point and fluidity of fat (i.e., 18:0 and cis-9 18:1).
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)